IDENTIFIKASI DAN KARAKTERISASI BAKTERI DOMINAN PENYEBAB KERUSAKAN BONTOT IKAN PAYUS (Elops hawaiensis) KOMERSIAL PADA SUHU PENYIMPANAN YANG BERBEDA - Ferina Gestiany; Sakinah Haryati; Achmad Noerkhaerin Putra; Dodi Hermawan (Leuit (Journal of Local Food Security), 2022)
Bontot is a jelly product processed from ladyfish (Elops hawaiensis) which has the characteristics of a savory taste. The aim of this study was to identify the types of bacteria that cause damage on bontot ladyfish on different storage temperatures. Bontot used in this study came from three different processing which is then stored for 2 days at different storage temperatures namely: room temperature (27 - 30oC), cold temperature (5-10oC) and freezing temperature 0oC to -5oC. The result showed that the three isolates dominant with code FD.R1 isolates suspected to contain Streptococcus sp. group D. For ID.D3 code and KR.B1 suspected bacterial types Plesiomonas sp.